Economic development and female labor participation in the Middle East and North Africa: A test of the U-shape hypothesis - Paolo Verme (IZA Journal of Labor & Development, 2015)
The Middle East and North Africa (MENA) region is known for having low female labor market participation rates compared with its level of economic development. A possible explanation is that countries in this region do not follow a U-shape relation between female participation and GDP during the process of economic development as initially proposed by Goldin (Investment in Women's Human Capital and Economic Development 1995) and observed elsewhere. This paper tests the U-shape hypothesis for the MENA region and finds that the region has outperformed other world regions in terms of the main drivers of the hypothesis, but there is no clear evidence of a U-shape.
Keywords: F66; J13; J16; J21; 330; Labor market; Participation models; Fertility; Economic transformation; Female education